Species delineation of the genus Diplazium Swartz (Athyriaceae) using leaf architecture characters (Bangladesh Journal of Plant Taxonomy, 2018)
The present study was conducted to delineate Diplazium Swartz species based on leaf architecture. Using PAleontological STatistics (PAST), a cluster and Principal Component Analysis of leaf architecture characters of 27 selected Diplazium species at the Philippine National Herbarium (PNH) was done. The dendogram (cophenetic correlation = 0.8436) and principal component analysis supported the four clusters of Diplazium using leaf architecture characters. At Gower distance of 0.25, Diplazium species were categorized as: Cluster 1 (Cladodromous – short stalked, stout and massive 1° vein); Cluster 2 (Reticulodromous – long stalked, moderate 1° vein); Cluster 3 (Craspedodromous – long stalked, stout to massive 1° vein); and Cluster 4 (Craspedodromous – short stalked, stout to massive 1° vein). The unifying characters were apex shape, base symmetry and 1° vein category, while the significant differentiating characters were 2° vein angle of divergence and variation in the 2° vein angle of divergence, 3° vein category, 3° vein angle of divergence, variation in 3° vein angle of divergence, 3° vein spacing and lobation. The successful delineation ofDiplazium species proved that leaf architecture can be a good taxonomic marker and could be an alternative way of identifying species in the absence of sori.